Configuration of Methylammonium Lead Iodide Perovskite Solar Cell and its Effect on the Device's Performance: A Review. Issue 19 (6th June 2022) - Dahal, Biplav; Li, Wenzhi
Abstract: In its initial phase in 2009, the inorganic‐organic hybrid perovskite solar cells (PSCs) delivered a 3.8% power conversion efficiency (PCE), which is far below the present 25.7% PCE obtained in 2022. The significant improvement of the efficiency of PSCs in such a short period has stimulated significant interest in the photovoltaic community. However, the performance of current PSCs is behind the commercially available and widely used solar cells in terms of stability and scalability. Among various commonly studied perovskite materials, methylammonium lead iodide (MAPbI3 ) is the most widely studied. This review will focus on the common solar cell structures (mesoporous, inverted planar p‐i‐n, planar n‐i‐p) using MAPbI3 perovskite as an active layer and the effect of these solar cell structures on their performances. Furthermore, some commonly‐used strategies are outlined for improving the device performance, such as optimizing the deposition technique of the charge transporting and the active layers, modifying the properties of the carrier transporting layer and the perovskite layer by interface engineering and doping, optimizing the perovskite surface morphology, along with others. This article will also discuss the hole transport free and electron transport free MAPbI3 PSCs. Abstract : MAPbI3 is the most widely studied perovskite material for different structures of perovskite solar cells (PSCs). The charge carrier transporting layer, electron transport layer, and hole transport layer play significant roles in the performance of the PSCs.